Pengaruh ewom di Instagram terhadap minat berkunjung dan dampaknya terhadap keputusan berkunjung wisatawan di Yogyakarta (studi kasus pada akun @explorejogja) - Yuliyani Yuliyani; Suharto Suharto (Journal of Tourism and Economic, 2022)
This research attempts to learn the influence of electronic word of mouthon visiting interest and tourist visiting decisions through the @explorejogja account. The sample in this study revealed 137 accounts that had become followers of the @explorejogja account which were randomly selected. The data collection method used in this study is to use a questionnaire. The data obtained were then processed using descriptive analysis and path analysis. The results of this study indicate that electronic news has an effect on visiting interest and has an impact on tourist visiting decisions. This is a tour from followers of @explorejogja who felt interested and then decided to visit the object uploaded to the @explorejogja account after seeing every photo, video and positive review.